ӨМНӨД МОНГОЛЫН ДУНД ЮРЫН УУР АМЬСГАЛ, ГЕОДИНАМИКИЙН НӨХЦӨЛ. II ХЭСЭГ: НАРИЙНСУХАЙТ ОРДЫН НҮҮРСНИЙ ГЕОХИМИЙН СУДАЛГАА - С., Батгэрэл; Б., Эрдэнэцогт; Н., Байгалмаа; Д., Алтанцэцэг (Geological Issues, 2021)
Based on the geochemistry of coal samples, collected from East and West mines of Nariinsukhait deposit, provenance, tectonic settings and source area-paleoweathering and paleoclimate was reconstructed. Sediments accumulated in peat swamp were mainly from acidic rocks mixed with smaller amount of intermediate rocks, indicated by Al2O3/TiO2 and A-K-CN diagrams. Seam 5 was deposited under realtively hot climate compared with upper seams (Seam 8, 9 and 10). Seam 5 is characterized by high Sr/Cu (avg. 7.4), Sr/Ba (avg. 2.5) and inertinite content (up to 35%). For upper seams, Sr/Cu (4.8), Sr/Ba (1.5) and inertinite content ( 14%) are low, indicating more humid climate and fresher water body. CIA, Ni/Co and V/Cr support the findings. In addition, сoal was deposited in foreland basin. Collision tectonic setting was dominant during Triassic and Jurassic period in southern Mongolia.